Feedback in Postgraduate Supervisory Communication: An Insight From Educators - Mazlina, Abdul Majid; Balsam, A. Mustafa; Noraziah, Ahmad (TOJQIH, 2014)
Postgraduate supervision is one of the most complex forms of teaching in higher education. Given the high rate of failure to complete postgraduate research, the quality of the research supervision has been questioned and some determinant factors leading to this undesirable outcome have been proposed like student’s expectations of the supervisor, supervisors’ insufficient knowledge, lack of interest in students’ work, and unsatisfactory ways of delivering feedback to the students’ work. Based on our experience as research supervisors and supervisees, we consider feedback significant in creating effective working relationship between the research supervisor and supervisee and supports successful completion of the research program. Different studies have investigated to what extent the supervisor’s feedback can be more effective in improving student’s performance and the type of feedback the students need. However, few studies have looked at how and why feedback is given as a supportive activity for students’ learning and development. This paper specifically focuses on how effective working communication between the research student and the supervisor can be achieved through the way feedback is given to the supervisee and how the student receives the feedback. The study concludes that the supervisors’ ability and the supervisee’s readiness to be open to criticism to provide and receive constructive feedback in a balanced way should lead to desirable academic outcomes in the academic context.